Decision Making Ability of Chilli Growers of Chhindwara District of Madhya Pradesh - Shrankhala Mishra , S.R.K.Singh , D.K.Singh , Sandeep Chouhan; N.Kumari (Indian Journal of Extension Education, 2014)
The study was conducted to assess the decision making ability of chili growers and to know the relationship between selected attributes of respondents and their decision making ability. Data were collected through interview method from randomly selected 120 farmer respondents. Age, area under crop, knowledge level, economic motivation, and use of information sources were found to be significantly related with decision making ability, while education, size of land holding, family income, farm power, extension participation and contact with extension agency had non-significant relationship with decision making ability. Irregular supply of electricity for irrigation, lack of storage and processing facility and lack of credit facility were the major constraints faced by the chili growers. The main suggestions given by the respondents were proper post-harvest processing through block and village level processing units and adequate warehouse facility should be provided by the government.